Investigating cardiovascular risk in premenopausal women on oral contraceptives: Systematic review with meta-analysis - Fabunmi, Oyesanmi A.; Dludla, Phiwayinkosi V.; Nkambule, Bongani B. (Frontiers in Cardiovascular Medicine, 2023)
Background: The use of oral contraceptives (OCs) is associated with an increased risk of cardiovascular events such as arterial and venous thrombosis (VTE). Cardiovascular diseases (CVDs) are the leading cause of death worldwide, with low- and middle-income nations accounting for over three-quarters of CVD deaths. The aim of the systematic review is to provide a comprehensive synthesis of the available evidence on the link between OC use and CVD-risk in premenopausal women and to further assess the role of geographic disparities in the reported prevalence of CVD-risk in women on OCs. Methods: A comprehensive search was conducted through the EBSCOhost search engine and MEDLINE, Academic Search Complete, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Health Source: Nursing/Academic Edition, were searched from inception till date. Cochrane Central Register of Clinical trials (CENTRAL) was also searched to augment relevant source of information. OpenGrey was searched and the reference list of the selected studies was also scanned. The potential risk of bias of included studies was assessed using the modified Downs and Black checklist. Data analysis was performed using the Review Manager (RevMan) version 5.3. Results: we included 25 studies which comprises of 3245 participants of which 1605 (49.5%) are OC users while 1640 (50.5%) are non-users. 15 studies were included for meta-analysis and the overall pooled estimates suggest a significant increased traditional cardiovascular risk variables (SMD = 0.73, (0.46, 0.99) (Z = 5.41, p < 0.001) and little to no difference in endothelia activation among OC users when compared with non-users (SMD = -0.11, (-0.81, 0.60) (Z = 0.30, p = 0.76). Europe (SMD = 0.03, (-0.21, 0.27), (Z = 0.25 p = 0.88) had the least effect size while North America had the highest effect size (SMD = 1.86, (-0.31, 4.04), (Z = 1.68 p = 0.09) for CVD-risks in OC users when compared with non-users. Conclusion: The use of OC suggest a significant increase in the prevalence of traditional cardiovascular risk variables with little to no difference in the risk of endothelia dysfunction when compared with non-users and the magnitude of CVD-risks varies across different geographical region.